Stafylokokové enterotoxiny - superantigeny schopné ošálit imunitní systém - Karamonová, Ludmila; Holubová, Barbora; Jelínková, Anna; Novotný, Jiří; Svobodová, Barbora (Chemické listy, 2019)
Staphylococcal food poisoning is one of the most common food-borne diseases worldwide. It is caused by the consumption of enterotoxins produced by toxigenic bacteria present in contaminated food. These toxins possess strong emetic and superantigenic activities. The aim of the review is to describe a characteristics of superantigens, their occurrence, and mechanism of action. An overview of methods capable to detect staphylococcal enterotoxins and the current EU legislation is also given.